DETERMINATION OF CRITERIA FOR THE EFFICIENCY OF AUTOMATION AND PRESENTATION OF RELATED FACTORS: DETERMINATION OF CRITERIA FOR THE EFFICIENCY OF AUTOMATION AND PRESENTATION OF RELATED FACTORS - Peeva, Svetla (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The object of definition of the present development are the criteria for efficiency from the implementation of automated equipment, and the accompanying risk assessment factors. The presentation of the three main variants of automation and their comparison with its social and economic efficiency, aims to facilitate the selection of the appropriate configuration of technological units to meet real human needs and protect business interests.